2000
DOI: 10.1007/s002109900155
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of mibefradil on contractions induced by sympathetic neurotransmitter release in the rat tail artery

Abstract: This study tested whether mibefradil exerts a stronger inhibitory effect than verapamil on sympathetic neurotransmitter release provoked by electrical field stimulation. Tail arteries (diameter 620+/-9 microm) were obtained from male Wistar rats. Ring segments of 2 mm length were mounted in an isometric wire myograph. After an appropriate period of equilibration and a priming procedure the vessels were either subjected to electrical field stimulation (EFS; frequency 0.25-4 Hz for 30 s) or a concentration-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Electrical stimulation has been shown to result in pronounced and reproducible increases of smooth muscle contraction [19] (Figure 2), which is sensitive to tetrodotoxin, guanethidine and prazosine, thus confirming the essential involvement of sympathetic nerves in the induction of this mechanical response. We used this particular preparation as it is densely innervated by sympathetic neurones.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Electrical stimulation has been shown to result in pronounced and reproducible increases of smooth muscle contraction [19] (Figure 2), which is sensitive to tetrodotoxin, guanethidine and prazosine, thus confirming the essential involvement of sympathetic nerves in the induction of this mechanical response. We used this particular preparation as it is densely innervated by sympathetic neurones.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study [19], we demonstrated that the contractile force evoked by EFS could be inhibited (>90%) by prazosin (0.1 lM) and abolished by tetrodotoxin (1 lM). Consequently, the contractions appear to be predominantly caused by stimulation-induced release of noradrenaline from the sympathetic nerve terminals.…”
Section: Experiments 2: Electrical Stimulationmentioning
confidence: 79%
See 2 more Smart Citations
“…Recently, a series of papers, using functional and electrophysiological approaches, have concluded that mibefradil may also block N-type VOCCs (Bezprozvanny and Tsien 1995;G枚thert and Molderings 1997;Molderings et al 2000;van der Lee et al 2000). In addition, in some human and rat CNS and rat spinal motoneurone preparations, mibefradil may inhibit other VOCCs including N, P…”
Section: Introductionmentioning
confidence: 97%